COMPARING OPEN DATA POLICIES AND THEIR IMPLEMENTATION IN DEVELOPED AND DEVELOPING COUNTRIES - Rininta Putri Nugroho (Jurnal Penelitian dan Pengembangan Komunikasi dan Informatika, 2014)
Around the world many countries have taken the initiative to encourage open data implementation. Policies are being developed and adapted as guidelines. The development is not seen to be balanced around the world because developing countries are still struggling with the formulation of usable policies and also the implementation. The question that needs to be answered is how comparing open data policies can help enhance the open data process. Another issue is whether or not a comparison is viable for the different characteristics of developed and developing countries. To answer this question a literature study is performed in the field of existing comparison frameworks and comparisons of e-government in developed and developing countries. From this study a framework can be derived to compare the open data policies of different countries and help overcome the difficulties that are faced in the open data process. Keywords : comparison framework, e-government, open data, open data policies, policy analysis